Registration of 'TAMO 411' Oat. Issue 2 (8th February 2018) - Ibrahim, Amir M. H.; Herrington, Rex; Sutton, Russell; Simoneaux, Bryan; Harrison, Stephen A.; Blount, Ann R.; Murphy, Paul; Barnett, Ron D.; Mason, Esten; Babar, Md A.; Duncan, Robert W.; Rudd, Jackie; et al.
Abstract : 'TAMO 411' (Reg. No. CV‐384, PI 675450) winter oat ( Avena sativa L.) was developed and released by Texas A&M AgriLife Research in 2012 based on the merits of its excellent grain yield, volume weight, forage potential, winter survival, and straw strength as compared to all recent Texas A&M AgriLife Research oat releases. It was also highly resistant to crown rust and moderately resistant to stem rust races prevalent in Texas during the time of its release. Authorized seed classes of TAMO 411 in the United States are breeder, foundation, registered, and certified. TAMO 411 was submitted for US Plant Variety Protection (PVP) under Public Law 91‐577 with the Certification Only option and a PVP certificate has been issued (Certificate No. 201500356).